Natural infection of Fasciola hepatica in cervids from Peru - Gomez-Puerta, Luis A. (2019)
Natural infection by Fasciola hepatica is recorded in a white-tailed deer (Odocoileus virginianus) and a taruca (Hippocamelus antisensis), both from the department of Cusco. Animals were remitted to the Veterinary Institute (IVITA-Maranganí, FMV, UNMSM) by the authorities of the National Service of Flora and Fauna (SERFOR, Cusco Headquarters). Six trematodes were collected from the bile ducts during the necropsy of the animals, and they were preserved in 70% ethanol. Morphological analysis indicated that they correspond to F. hepatica. This was confirmed by analyzing of the mitochondrial DNA of the parasites by partially amplifying the cytochrome c oxidase subunit 1 (cox1) and the NADH dehydrogenase subunit 1 (nad1) genes. Analysis of these genes had an identity greater than 99% compared to genes from GenBank. The present study demonstrates the occurrence of F. hepatica in these cervids, thus adding two new definitive hosts for the parasite.